Galileo's dialogue - Malone, Adrian; Sutherland, Donald; Minor, Dale.; LeBrun, Nancy; Corens, Kalindi; MacLowry, Randall; Discovery Channel (Firm).; Discovery Communications, Inc.; Discovery Networks; Cronkie Ward Company (Bethesda, Md. Discovery Communications, 1997)
This program tells the story surrounding Galileo's book from the revelation of the Copernican view that the sun, and not the earth, is the center of the universe to the trial of Galileo before the Holy Office. This drama pits egotistical visionary Galileo against the bullheaded Pope Urban VIII and science versus theology.
Series producer: Dale Minor ; Executive Producer Discovery Networks: Nancy LeBrun ; Associate producer: Kalindi Corens ; Editor: Randall MacLowry.
Narrated by Donald Sutherland.
Actors: Bill Toscano, Michael Pizzi, David Bryan Jenkins, Enrico Panzarelli, Gino Manninni and John Spears.
VCD.
Keywords: Galilei, Galileo -- 1564-1642.; Astronomy -- Philosophy; Astronomy -- History